Research workshop - Joseph, Corina (UiTM Sarawak, 2016)
The Centre of Graduate Studies organised a one-day Research Workshop in collaboration with the International Research Symposium in Service Management (IRSSM 6) on 11th August 2015, at the Riverside Majestic Hotel, Kuching Sarawak. The main objective of this workshop was to provide insights on research and publication skills related to business and service management among the postgraduate students. The workshop was attended by approximately 50 postgraduate students.